USING GROUP DISCUSSION TO IMPROVE STUDENTS’ SPEAKING FLUENCY - Ibnu Wahyurianto (Journal of English for Academic and Specific Purposes (JEASP), 2018)
Being able to speak in target language is considered as the indicator thatevery language learner is mastering the target language. Likewise inEnglish, the learners are regarded mastering English when they canproduce the sound of English itself in the form of good communicationtoward the others. Nevertheless, teaching English is a complex process,since it involves some activities started from preparation until evaluation.In addition, there are some barriers regarding teaching speaking, i.e thenumber of students, teacher’s competence, and even students’ problems.Although teaching speaking is a kind of difficult job, still there is a way toovercome some stated problems; group discussion. So, this research isaiming at the implementation of group discussion to improve students’speaking fluency. To achieve the research objectives, the design of theresearch is classroom action research which involves four steps, they areplanning, implementing, observing, and reflecting. The subject research isthe students of Bahasa Indonesia Department semester II of University ofMuhammadiyah Malang who have different English proficiencybackground. Data collection method used is preliminary observation,indepth interviews, participatory observation, and documentation. Thedata gathered will be analyzed by using the qualitative analysis involvingreducing data, displaying data, verifying data and taking conclusion. Basedon the results, it can be stated that the implementation of groupdiscussion in speaking course can improve the students’ speaking fluency.